Comparison of seminal characteristics of Aberdeen Angus, Holstein and Nelore bulls before and after cryopreservation (Research, Society and Development, 2021)
The aim of this study was to evaluate parameters indicative of sperm quality of fresh and post-thawed semen of Aberdeen Angus, Holstein and Nelore bulls. Thirty-nine bulls were used: Aberdeen Angus (n=13), Holstein (n=13) and Nelore (n=13). The ejaculate collects were performed twice a week using artificial vagina, totaling 792 semen collections, 307 for Aberdeen Angus, 225 for Holstein and 260 for Nelore bulls. After collection, fresh semen was evaluated and semen freezing was performed. After freezing, the batches were thawed and progressive motility was determined. The analysis of fresh semen showed that there was no difference (P = 0.053) between the Aberdeen Angus and Nelore breeds, while ejaculates from Holstein bulls showed a statistical difference (P = 0.024). As well, a difference (P